THE EFFECT OF INVESTMENT DECISIONS, CAPITAL INTENSITY, POLLITICAL CONNECTION AND CAPITAL STRUCTURE ON FIRM VALUE IN PUBLIC STATE-OWNED COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2019-2022 - Sri Handayani; Nihlatul Qudus Sukma Nirwana (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This study aims to determine the Influence of Investment Decisions, Capital Intensity, Political Connection and Capital Structure on Company Value in State-Owned Enterprises Listed on the Indonesia Stock Exchange in 2019-2022. Method: This research is a type of quantitative research, the sampling method used is the purposive sampling method, the number of companies sampled in this study is 23 State-Owned Enterprises Listed on the Indonesia Stock Exchange in 2019-2022, the data source used is secondary data, and the data analysis method used in this study is Multiple Linear Regression with SPSS version 27 data processing tools. Results: The results of this study indicate that Investment Decisions Affect Company Value, Capital Intensity Affects Firm Value, Political Connection Affects Firm Value, and Capital Structure Affects Firm Value. Novelty: This study provides empirical evidence regarding the simultaneous influence of Investment Decisions, Capital Intensity, Political Connection and Capital Structure on Company Value in State-Owned Enterprises, specifically within the 2019-2022 period.